Comparing media systems beyond the Western world - Hallin, Daniel C.; Mancini, Paolo (Cambridge : Cambridge University Press, 2012)
'Comparing Media Systems Beyond the Western World offers a broad exploration of the conceptual foundations for comparative analysis of media and politics globally. It takes as its point of departure the widely used framework of Daniel C. Hallin and Paolo Mancini's Comparing Media Systems, exploring how the concepts and methods of their analysis do and do not prove useful when applied beyond the original focus of their'most similar systems' design and the West European and North American cases it encompassed. It is intended both to use a wider range of cases to interrogate and clarify the conceptual framework of Comparing Media Systems and to proposed new nidels, concepts, and with processes of political transition. Comparing Media Systems Beyond the Western World covers, among other cases, Brazil, China, Isreal, Lebanon, Poland, Russia, Saudi Arabia, South Africa, and Thailand'--
Includes bibliographical references and index.
Keywords: Mass media -- Political aspects -- Developing countries; Mass media -- Political aspects -- Developing countries -- Case studies; Mass media -- Social aspects -- Developing countries -- Case studies; Mass media policy -- Developing countries -- Case studies